High-resolution radiation mapping to investigate FDNPP derived contaminant migration. (November 2016) - Martin, P.G.; Payton, O.D.; Yamashiki, Y.; Richards, D.A.; Scott, T.B.
Abstract: As of March 2016, five years will have passed since the earthquake and ensuing tsunami that crippled the Fukushima Daiichi Nuclear Power Plant on Japan's eastern coast, resulting in the explosive release of significant quantities of radioactive material. Over this period, significant time and resource has been expended on both the study of the contamination as well as its remediation from the affected environments. Presented in this work is a high-spatial resolution foot-based radiation mapping study using gamma-spectrometry at a site in the contaminated Iitate Village; conducted at different times, seventeen months apart. The specific site selected for this work was one in which consistent uniform agriculture was observed across its entire extent. From these surveys, obtained from along the main northwest trending line of the fallout plume, it was possible to determine the rate of reduction in the levels of contamination around the site attributable to the natural decay of the radiocesium, remediation efforts or material transport. Results from the work suggest that neither the natural decay of radiocesium nor its downward migration through the soil horizons were responsible for the decline in measured activity levels across the site, with the mobilisation of contaminant species likely adhered to soil particulate and the subsequent fluvial transport responsible for the measurable reduction in activity. This transport of contaminant via fluvial methods has already well studied implications for the input of contaminant material entering the neighbouring Pacific Ocean, as well as the deposition of material along rivers within previously decontaminated areas. Highlights: Time resolved radiation distribution studied. Attenuation through downward migration quantified. Reduction in activity levels via transport examined. Attenuation and transport possible sources of activity reduction.